2014
DOI: 10.2174/1874262901408010069
|View full text |Cite
|
Sign up to set email alerts
|

Processing of Multispectral ASTER Data for Mapping Alteration Minerals Zones: As an Aid for Uranium Exploration in Elmissikat-Eleridiya Granites, Central Eastern Desert, Egypt

Abstract: Elmissikat-Eleridiya district is one of the most important uranium localities in the central Eastern Desert of Egypt. The feature oriented principal component selection (FPCS) and spectral angle mapper (SAM) techniques were applied on ASTER L1B imagery for mapping the common alteration zones. The study revealed that ASTER VNIR-SWIR bands are effectively used for delineating sericite, kaolinite, chlorite, illite and hematite bearing alteration zones, whereas ASTER TIR bands are most effective in delineation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Using USGS library spectra to identify the high and low reflectance bands for each mineral in VNIR-SWIR bands of ASTER satellite data. The proposed minerals association was chosen according to the previous studies and observations in the area as the main association for the uranium mineralisation (El-Mansi 1993; Moghazi 2002;Abdelrahman 2014;Elsaid et al 2014;Gaafar and Aboelkhair 2014). Matched Filtering (MF) algorithm was used to identify the alteration zones of the selected minerals using the USGS mineral reference spectra.…”
Section: Mineral Spectral Mappingmentioning
confidence: 99%
See 1 more Smart Citation
“…Using USGS library spectra to identify the high and low reflectance bands for each mineral in VNIR-SWIR bands of ASTER satellite data. The proposed minerals association was chosen according to the previous studies and observations in the area as the main association for the uranium mineralisation (El-Mansi 1993; Moghazi 2002;Abdelrahman 2014;Elsaid et al 2014;Gaafar and Aboelkhair 2014). Matched Filtering (MF) algorithm was used to identify the alteration zones of the selected minerals using the USGS mineral reference spectra.…”
Section: Mineral Spectral Mappingmentioning
confidence: 99%
“…It represents an important example of younger granites (monzogranite and syenogranite) within the Arabian Nubian Shield. Airborne gammaray spectrometry revealed that the syenogranitic bodies have the highest radioactivity related to shear zones usually filled with silica veins and an abnormal radioactivity with visible uranium mineralisation they are denser and closely spaced in the northern granitic mass of G. El-Missikat than those at the southern mass of G. El-Eridiya (Elsaid et al 2014). Several geological studies have been investigated the area and showing its radioactivity importance (Ammar 1973; Bakhit 1978;El Tahir 1985;Abu Dief 1993;El-Mansi 1993;Moghazi 2002;Gaafar and Aboelkhair 2014) The aim of this study is to combine and to analyse the previous generated spatial data layers (ASTER imagery, Airborne gamma-rays and minerals' reflectance spectrometry) using mathematical and quantitative data models and to produce potential radioactivity zones for the discriminated uraniferous granite of El-Missikat, El-Eridya and Kab Amiri areas in the Central Eastern desert, that will assist in the further mineral exploration and evaluation studies.…”
Section: Introductionmentioning
confidence: 99%
“…Threshold function used in many types of Spectral minerals algorithms such as procedures based on the interpretation of Spectral knowledge, methods to identify the ultimate goal or the distribution of pixels extractive for maping minerals and rocks. The threshold calculation statistical methods lead to low concentrations removal [22]. At first, the pixel value of each image sets from zero to 255 and then threshold calculation is done using Equations (2)- (4) with 98%, 95% and 92% confidence level.…”
Section: Data Processing Of the Study Areamentioning
confidence: 99%
“…Deploying ASTER multispectral data in mapping mineral alteration is a well-documented procedure (e.g. Ferrier and Wadge 1996;Ferrier et al 2002;Heswon et al 2005;Rowan et al 2005;Pour and Hashim 2011;Hosseinjani and Tangestani 2011;Tayebi et al 2013;Cudahy 2012;Elsaid et al 2014;Testa et al 2018;Sekandari et al 2020). Band Ratio on ASTER multispectral data has been utilized to identify alteration associated with ferric iron oxides mineral group like hematite and goethite as well as silicification (Cudahy and Ramanaidou 1996;Rowan and Mars 2003;Rowan et al 2005;Heswon et al 2005;Cudahy et al 2008;Cudahy 2012;Haest et al 2012).…”
Section: Introductionmentioning
confidence: 99%